Removal of Pb2+ Ion from Industrial Wastewater by New Efficient Biosorbents of Oyster Plant (Tradescantia spathacea Steam) and Negkassar Leaf (Mammea siamensis T. Anderson) - Kannika Keawkim (Science Faculty of Chiang Mai University, 2019)
This work, low-cost biosorbents were prepared from Oyster plant (OP) and Negkassar leaf (NL) for lead (Pb2+) removal. The chemical structures of sorbents were characterized by FT-IR and elemental analyzer (CHN). All experiments were conducted in a batch system. The pH (2-7) of a solution, contact time (15-180 min), the dosage of biosorbent (0.25-3.00 gdm-3) and the initial metal concentration (2-75 mg dm-3) were optimized. The adsorption kinetic of Pb2+ on sorbents was performed using pseudo-first-order and pseudo-second-order model. Results are good agreement with pseudo-second-order, which described that the mechanism is controlled by chemical adsorption. The adsorption process was examined by Langmuir and Freundlich isotherm. The Langmuir isotherm gave a better fit than the Freundlich isotherm. It can be implied that the single layer sorption of Pb2+ occurs on the sorbent surface. The maximum adsorption capacity (qmax) of Pb2+ on OP and NL is 161.29 and 104.17 mg g-1, respectively. In addition, the effective sorbent of OP and NL can be applied to remove Pb2+ from wastewater samples.